By-product hazelnut seed skin characteristics and properties in terms of use in food processing and human nutrition - Marcin Kruk; Alicja Ponder; Joanna Horoszewicz; Damian Popławski; Katarzyna Król; Joanna Leszczyńska; Danuta Jaworska; Monika Trząskowska (Scientific Reports)
Abstract The hazelnut seed skins (HSS) are by-products from roasting or blanching hazelnuts without direct second utilization. The generation of HSS creates an economic and environmental problem. The object of the study was a comprehensive analysis of the properties for reuse of HSS. Water extraction of industrial HSS was applied (water with sonication of the HSS for 10 min at 90 ℃). The extracts obtained were freeze-dried to facilitate analysis and future application. The HSS and their extracts were analysed. Polyphenols, antioxidants, allergens, antimicrobial properties and instrumental sensory analysis were examined. The total polyphenol content in the samples was 37.8–44.0 mg gallic acid equivalent g−1. Gallic acid was the major phenolic compound. The antioxidant capacity of the samples was 198.9–250.6 mg VCEAC g−1 (vitamin C equivalent) according to the ABTS method and 98.4–106.8 mg VCEAC g−1 in the DPPH method. The extracts inhibited all tested strains of pathogenic bacteria. Allergen content was reduced in HSS and the extracts. Instrumental sensory analysis showed differences between taste parameters and odour profile samples. HSS can be reused in food production as a bacteriostatic, antioxidant additive and sensory-creating factor due to various chemical compounds corresponding with taste and odour.